Pengaruh Profitabilitas, Ukuran Perusahaan dan Pertumbuhan Penjualan terhadap Struktur Modal pada Perusahaan Telekomunikasi Tahun 2020-2023 - Erlin Priscila Ariyani (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
The growth of sales in the information and telecommunications sector has decelerated, which can impact a company's capital structure. A decline in company sales or revenue tends to negatively affect profitability. As revenue decreases due to slower sales growth, companies often resort to increased debt usage, ultimately altering their capital structure. This study aims to determine the influence of profitability, company size, and sales growth on the capital structure of telecommunications companies listed on the Indonesia Stock Exchange from 2020 to 2023. Purposive sampling was employed to select 48 telecommunications companies meeting specific criteria. Data analysis was conducted using multiple linear regression analysis with statistical software. The results indicate that profitability has a negative and significant impact on capital structure, while company size and sales growth both have positive and significant effects on capital structure.